Determinasi Pelanggan Potensial Memanfaatkan Meta Ads Campaign: Studi Kasus MinMax Coffee - Arfan Farokhi; Tsiqotun Affan Maulana; Deru R. Indika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This final project aims to identify the most relevant potential customer segments for MinMax Coffee by utilizing digital advertising campaigns through Meta Ads. By conducting an experimental approach with multiple ad sets targeted based on age range and audience interests, this project analyzed performance data such as click-through rate (CTR), cost per click (CPC), and engagement metrics to determine the most responsive segment to the campaign. The results indicate that the ad set targeting the 25–35 age group (Ad Set 2) demonstrated the best performance, achieving the highest CTR of 1.62% and the lowest CPC of IDR 533, outperforming the 21–24 age group, which although had a wider reach, showed lower interaction. Moreover, the combination of interests such as coffee, social media, music, and hangout activities proved to yield better interaction rates than audiences with interests limited to coffee and studying or working. These findings suggest that marketing budgets should be more focused on the 25–35 age segment and that enhancing visual formats and copywriting can improve ad effectiveness in other segments. Further recommendations include applying retargeting ads to reach users who interacted with the ads but did not convert, and performing routine ad performance analysis to refine strategies using up-to-date data. This data-driven approach enables MinMax Coffee to craft a more accurate and cost-effective digital marketing strategy to attract potential customers.